Uncommon isolated near total small bowel mesenteric tear after blunt abdominal trauma and successful damage control surgery - Sundara, Chakravarthy Didde; Balaga, Venkatarao; Gandeti, Kirankumar; Yeddula, Venkata Jayaramudu; Gera, Arjuna (International Journal of Research in Medical Sciences, 2017)
Isolated near total small bowel mesenteric tear after blunt abdominal trauma is rare. We reported here an uncommon case with isolated near total small bowel mesenteric tear after blunt abdominal trauma. Early diagnosis of mesenteric tear is important and enhanced computed tomography is more sensitive for that kind of injury. Damage control laparotomy should be considered if unstable vital signs occurred.